EKOSISTEM MANGROVE PERAIRAN TELUK KWANDANG KABUPATEN GORONTALO UTARA - Olii, Abdul Hafidz; Muhlis, Muhlis; Sayuti, Sayuti (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
In many coastal waters, including in the Kwandang Bay, often there are threeinterrelated ecosystems, they are mangroves, seagrass beds and coral reefs ecosystems.This study aims to determine the existence of mangrove ecosystems in the KwandangBay waters, and to determine the condition of the ecosystem based on the communitystructure. This research was conducted in the waters in the Kwandang Gulf of NorthGorontalo District for three months. The method used in this research was a surveymethod, and purposive sampling was conducted to collect the data. Six samplingstations with 20x20 m2 transect areas were determined to collect the mangroveecosystem data. Mangrove species found were Shoneratia alba, Brugeiragymnorrhiza, Xylocarpus sp,, Cariops tagal, Rhizophora sp, and Avicenia sp. Themangrove ecosystem has low diversity level, evenly distributed species, and there is nodominant species.